Molecular role of peptides/proteins in subfertility of polycystic ovarian syndrome - Celik, Onder; Aydin, Suleyman; Celik, Nilufer; Ugur, Kader; Yavuzkir, Seyda; Hatirnaz, Safak; Celik, Sude (C M B Assoc, 2019)
Obesity and hyperandrogenemia are known to have adverse effects on both developing follicle and endometrium receptivity in polycystic ovarian syndrome (PCOS). Insulin resistance also contributes to this dilemma as a cause or a consequence and leads to worsening of the clinical picture. The difficulty in obtaining pregnancy despite the presence of a large number of oocyte has concentrated our attention on oocyte quality and development. However, the occurence of subfertility has also caused us to investigate the presence of different etiologic agents in non-obese PCOS women with normal androgen and insulin levels. In this context peptides have become the most accused and investigated molecules in cases of impaired fertility due to PCOS. Most of the studies investigating the relationship between PCOS and peptide did not support each other. The difficulties in measuring peptide levels as well as the individual variations in peptide synthesis and release are possible causes of this incongruity. For all these reasons, the incorporation of studies investigating the relationship between PCOS, peptide and subfertility in an article has become critical to pioneering future work. Understanding the association between peptides and subfertility will help us to understand the effects of peptides on failed fertility in PCOS. Moreover, updating our knowledge about peptides may allow us designing new drugs to to treat subfertility in PCOS. This review provides a general summary of the mechanisms of action of neuroendocrine peptides in regulating reproductive events. Since it is not usual to discuss all peptides in this context, only the effects of key central and peripheral peptides on fertility in PCOS have been extensively addressed.
Keywords: Peptides; PCOS; Subfertility